Solvent Effect on the Fabrication and Mechanical Behavior of Sandwich Structured Poly(vinyl alcohol)/Carbon-nanofiber Buckypaper Composite. Issue 8 (October 2016) - Lu, M.; Sun, S.C.; Bu, Z.X.; Wang, L.S.; Sun, L.
A solution-casting method has been developed to fabricate polymer/carbon nanofiber (CNF) buckypaper composite/polymer sandwich structures. Such layered nanocomposites can take advantage of the buckypaper's mechanical reinforcement effect and to introduce multi-functionalities including dynamic damping, electrical/thermal conductance and electromechanical responses. By controlling the solution chemistry, the structure, morphology and thus the performances of the composite samples were effectively manipulated. Dimethyl sulfoxide (DMSO) as a solvent was found to greatly enhance the wettability of polyvinyl alcohol (PVA) to carbon nanofiber as compared to water, and it increased polymer penetration in the buckypaper. It was also observed that PVA formed a surface coating layer surrounding individual CNF which behaved differently from bulk polymer. This intermediate layer played a critical role in determining the static mechanical reinforcement effect of buckypaper and further affected the composite dynamic damping characteristics. Incorporating carbon nanofiber buckypaper not only strengthened the PVA static mechanical performance but also lowered the loss modulus and tan d. By introducing the controlled structure of such composite sandwiches, it is possible to tailor the multi-functionalities targeting specific applications.